Artificial Intelligence and Business Education: Transformation, Challenges, and Future Prospects - FENGRUI, ZHANG (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
The rapid advancement of Artificial Intelligence (AI) has triggered a paradigm shift across global industries, with business ecosystems undergoing unprecedented transformations in decision-making, operations, and talent demands. Against this backdrop, business education—tasked with nurturing future business leaders and professionals—faces both urgent imperatives and unprecedented opportunities. This paper systematically explores the integration of AI into business education, focusing on four core dimensions: the practical applications of AI in reshaping teaching models, the core value of AI-driven business education reform, the multifaceted challenges encountered in implementation, and actionable strategies for sustainable development. Drawing on case studies from leading business schools (e.g., MIT Sloan, Tsinghua SEM) and industry reports (McKinsey, World Economic Forum), the paper argues that AI is not merely a technical tool but a foundational driver for redefining the goals, content, and methods of business education. By addressing issues such as technological limitations, ethical risks, and educational inequities, business education can leverage AI to cultivate复合型 (interdisciplinary) talents equipped with both business acumen and AI literacy, ultimately aligning with the needs of the intelligent era. The paper concludes with a vision for the future of AI-integrated business education, emphasizing the importance of collaboration among universities, enterprises, and policymakers to build an inclusive, innovative, and future-oriented educational ecosystem.